Embedding information on additively manufactured parts using Mondrian patterns (Journal of Additive Manufacturing Technologies, 2021)
With Additive Manufacturing (AM), parts having complex geometries can be produced easily compared to the traditional manufacturing methods. AM gives the opportunity to produce those complex parts in a very straightforward manner. This simplification creates the capability of embedding different structures, patterns or assets to the part without the burden of additional manufacturing processes. It has been observed that the most common approach for this purpose is to use QR codes. This article discusses a different method combining science and art together. A simple coding approach inspired by the Dutch painter Mondrian, who is known to have paintings consisting of grids and contrast colors, has been developed. In this paper, details of the proposed method to embed information onto the AM parts are presented and results are discussed.
Keywords: : Additive manufacturing; embedding information; Mondrian; FFF